CluM: A clustering-cum-Markov model for resource prediction in a data center - Govindarajan, Madhupriya; Selvaraj, Mercy Shalinie; Ravi, Nagarathna (Zielona Góra: Uniwersytet Zielonogórski)
High-end data centers are required to process the user requests and provide them with a better quality of service. The prominent issues in building a sustainable data center are reduced carbon footprint, dynamic capacity planning to reduce resource provisioning time and cost, minimized virtual machine migration to prevent higher downtime and enhanced return on investment and resource utilization.
Keywords: data center; Markov model; randomized algorithms; resource prediction; workload characterization